Microbial Contamination in Chicken Meat in Traditional Markets in Banyuwangi - Wibawati, Prima Ayu; Chrismonica, Yunia; Susanti, Racca Biana; Himawan, Mario Putra; Devy, Afaf Heny Sintya; Nirmalasari, Juwita Ayu; Abdramanov, Abzal (Universitas Airlangga, 2024)
This study aimed to analyze the microbial contamination of chicken meat and its pH value from traditional markets in Banyuwangi, East Java to ensure public health. A total of 30 raw chicken meat samples from three traditional markets were used in this study and examined for the presence of Escherichia coli and Salmonella spp. E. coli and Salmonella spp. were identified using Gram staining, culturing, and biochemical tests. The Most Probable Number (MPN) method was used for coliform and E. coli. Measuring the pH value of chicken meat was carried out after purchasing the meat and 24 hours after storage at cold temperatures. The results showed coliform contamination in all samples with an average of >1100 CFU/G with E. coli contamination of 20% (6/30), exceeding the maximum recommended limit. Furthermore, the identification of Salmonella spp. in all samples showed negative results. Chicken meat pH value decreased with the length of postmortem time; immediately after purchase (0 hours), the pH value was 5.78 ± 0.26, and after 24 hours of storage, it raised 6.02 ± 0.28. In conclusion, there was high coliform contamination out of 30 raw chicken meat samples taken from some traditional markets in Banyuwangi. Furthermore, E. coli contamination was as much as 20%, and Salmonella spp. was negative.